Current trends in biopolymers for food packaging: a review - González-López, Martín Esteban; Calva-Estrada, Sergio de Jesús; Gradilla-Hernández, Misael Sebastián; Barajas-Álvarez, Paloma (Frontiers in Sustainable Food Systems, 2023)
Non-biodegradable plastics have been extensively used for food packaging due to their outstanding properties that preserve food quality during transportation and shelf-life. The global awareness of plastic pollution has led to the development of environmentally friendly technologies for food packaging such as biodegradable polymers, edible films and coatings, and active or smart packaging. However, the petroleum-based polymers market seems not to be interested in setting back and current waste management strategies continue to be deficient in both technical and economic aspects. This work aimed to provide insights into the state-of-the-art technologies for food packaging based on the advances that have been made to improve the moisture, heat, and barrier properties of novel materials that could close the gap to conventional plastics in terms of performance and costs. This literature review takes a multidisciplinary approach, focusing on the required properties of food packaging and the potential impact on the physicochemical properties of food products. The aim is to identify gaps between current technologies and market demand that impede the alignment of the food packaging industry with global environmental policies. Several sustainable packaging options were identified, such as biopolymers like PLA or PBAT. However, most successful packaging solutions are made up of PVA, chitosan, gelatin, or films based on proteins. In both cases, the addition of essential oils, natural extracts, or nanoparticles to the packaging material has demonstrated its effectiveness in improving performance and ensuring food preservation over an extended period on the shelf. However, a significant research gap has been identified regarding the scaling up of packaging materials based on natural polymers, despite the technology appearing to be sufficiently advanced for practical implementation. Hence, it is necessary not only to optimize parameters to enhance functionality and mechanical properties but to demonstrate their feasibility for industrial production. Furthermore, it is essential to assess their environmental impact. It is important to provide evidence of the feasibility of real-world applications of the new materials developed, demonstrating their effectiveness under critical storage conditions for the preservation of different food groups.